2018
DOI: 10.1111/sjtg.12242
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal wetland changes and their threats in North Central Ethiopian Highlands

Abstract: Wetlands are important environmental resources for rural livelihoods in Ethiopia. The study investigated spatiotemporal change of wetlands, drivers and effects in North Central Ethiopian Highlands. Landsat satellite imageries of 1984, 1993, 2000, and 2013 were used to analyse wetland changes over the last three decades. Practical observations, interviews and discussions with local communities and officers were also conducted to address the main objective. Furthermore, secondary data on crop yields were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…In other words, the city's population has increased by 761% which is equivalent to 11,591 people/year in the past 36 years. Similar trends were reported in other studies (Hurni et al 2005;Gebrelibanos and Assen 2015;Gashaw et al 2017;Hussien et al 2018;Berihun et al 2019;Degife et al 2019;Desta and Fetene 2020;Hailu et al 2020).…”
Section: Driving Forces Of Lulc Changessupporting
confidence: 91%
“…In other words, the city's population has increased by 761% which is equivalent to 11,591 people/year in the past 36 years. Similar trends were reported in other studies (Hurni et al 2005;Gebrelibanos and Assen 2015;Gashaw et al 2017;Hussien et al 2018;Berihun et al 2019;Degife et al 2019;Desta and Fetene 2020;Hailu et al 2020).…”
Section: Driving Forces Of Lulc Changessupporting
confidence: 91%
“…The area has large upstream water potential sites, intensive irrigable downstream lands, and high hydropower potential (Dibaba et al, 2020). Previous studies in southwestern Ethiopia have documented a decline in wetland resources due to environmental pressure and human stresses (Berhanu et al, 2021; Dibaba et al, 2020; Dixon et al, 2021; Hussien et al, 2018). The study area has different LULC classes: cultivated land, forest, grassland, shrubs land, and settlements.…”
Section: Methodsmentioning
confidence: 99%
“…Due to different geographical locations, regional natural and socio-economic conditions are different, the impact on wetland changes varies greatly. Studies have shown that in areas with high population pressure, such as Ethiopia in Africa and Hangzhou Bay in China, reclaiming wetlands is a response to the rapid population growth [ 55 , 56 ]. In the agriculturally developed areas such as Northeast China, reclaiming wetlands is an inevitable choice for agricultural production [ 17 ].…”
Section: Discussionmentioning
confidence: 99%